Combined thermal and herbicide stress in functionally diverse coral symbionts. (September 2015) - van Dam, J.W.; Uthicke, S.; Beltran, V.H.; Mueller, J.F.; Negri, A.P.
Abstract: Most reef building corals rely on symbiotic microalgae (genus Symbiodinium ) to supply a substantial proportion of their energy requirements. Functional diversity of different Symbiodinium genotypes, endorsing the host with physiological advantages, has been widely reported. Yet, the influence of genotypic specificity on the symbiont's susceptibility to contaminants or cumulative stressors is unknown. Cultured Symbiodinium of presumed thermal-tolerant clade D tested especially vulnerable to the widespread herbicide diuron, suggesting important free-living populations may be at risk in areas subjected to terrestrial runoff. Co-exposure experiments where cultured Symbiodinium were exposed to diuron over a thermal stress gradient demonstrated how fast-growing clade C1 better maintained photosynthetic capability than clade D. The mixture toxicity model of Independent Action, considering combined thermal stress and herbicide contamination, revealed response additivity for inhibition of photosynthetic yield in both tested cultures, emphasizing the need to account for cumulative stressor impacts in ecological risk assessment and resource management. Highlights: Water quality influences thermal stress thresholds in different Symbiodinium types. Photosystem of clade D tested more sensitive than C1 to a common herbicide. Increased thermal tolerance quickly countered in presence of herbicide. Mixture toxicity approach demonstrated response additivity for combined stressors. Symbiotic partnership may be compromised in areas subjected to terrestrial runoff. Abstract : Thermal-tolerant Symbiodinium type D tested especially vulnerable to a common herbicide, emphasizing the significance of cumulative stressors in ecological risk management.